La integración regional sudamericana: de la adolescencia a la madurez (Tema Central) - Scotton, Damiano (2021)
Along its history, the South American subcontinent has demonstrated strong wishes oriented to regional integration, and particularly starting from 1960 with the foundation of the “Asociación Latinoamericana de Libre Comercio” (ALALC). However, until nowadays, the main actors in the continental landscape keep being the national states, while the regional organizations created until now have become more or less effective spaces of dialogue between countries or even reached their complete failure. The present article takes as its main objective that of demystify those that I consider “false obstacles” to regional integration, pointing then out those which I consider real limits hindering a concrete, deep and mature cooperation between south American countries and, finally, proposing some possible solutions for south American regional integration to pass from its current “adolescence” to a complete maturity.